Literature Review Faktor Individu, Organisasi dan Lingkungan Kerja Terhadap Kejadian Burnout Syndrome dan Kepuasan Kerja Perawat - Puji Melasi; Catharina Dwiana Wijayanti (IPM2KPE, 2023)
This study aims to determine how much influence individual, organizational and work environment factors have on the incidence of burnout syndrome and job satisfaction of nurses in hospitals. This research method uses a literature study method analyzed from several journals, which are related to the topic taken. The results obtained vary, but the majority of research results show that individual, organizational and work environment factors greatly influence burnout syndrome. Individual, organizational and work environment factors contribute to the incidence of burnout syndrome. In conclusion, Burnout syndrome has a negative effect on job satisfaction, meaning that the lower the burnout syndrome, the higher the nurse's job satisfaction. This is because the high performance of nurses causes the level of job satisfaction to increase so that it can reduce burnout syndrome that occurs in nurses. Meanwhile, organizational factors and environmental factors have a positive influence on job satisfaction, so the better the organizational factors and environmental factors, the greater the level of nurse job satisfaction. This is because a supportive work situation and support from superiors and co-workers are able to motivate nurses to develop themselves well while working at the hospital so that the level of job satisfaction increases. Keywords: Burnout, Individual Factors, Environment, Organizational Job Satisfaction